Dystroglycan Mediates Clustering of Essential GABAergic Components in Cerebellar Purkinje Cells - Briatore, Federica; Pregno, Giulia; Di Angelantonio, Silvia; Frola, Elena; De Stefano, Maria Egle; Vaillend, Cyrille; Sassoè-Pognetto, Marco; Patrizi, Annarita (Frontiers in Molecular Neuroscience, 2020)
Muscle dystrophin-glycoprotein complex (DGC) links the intracellular cytoskeleton to the extracellular matrix. In neurons, dystroglycan and dystrophin, two major components of the DGC, localize in a subset of GABAergic synapses, where their function is unclear. Here we used mouse models to analyze the specific role of the DGC in the organization and function of inhibitory synapses.Loss of full-length dystrophin in mdx mice resulted in a selective depletion of the transmembrane bDystroglycan is a GABAergic synaptic organizer dystroglycan isoform from inhibitory postsynaptic sites in cerebellar Purkinje cells. Remarkably, there were no differences in the synaptic distribution of the extracellular a-dystroglycan subunit, of GABAA receptors and neuroligin 2. In contrast, conditional deletion of the dystroglycan gene from Purkinje cells caused a disruption of the DGC and severely impaired postsynaptic clustering of neuroligin 2, GABAA receptors and scaffolding proteins. Accordingly, whole-cell patch-clamp analysis revealed a significant reduction in the frequency and amplitude of spontaneous IPSCs recorded from Purkinje cells. In the long-term, deletion of dystroglycan resulted in a significant decrease of GABAergic innervation of Purkinje cells and caused an impairment of motor learning functions. These results show that dystroglycan is an essential synaptic organizer at GABAergic synapses in Purkinje cells.